2014
DOI: 10.1371/journal.pone.0095463
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Gene Polymorphism and Risk for Coronary Heart Disease in the Chinese Population: A Meta-Analysis of 61 Studies Including 6634 Cases and 6393 Controls

Abstract: BackgroundNumerous studies have evaluated the association between the apolipoprotein E (apoE) gene polymorphisms in coronary heart disease (CHD). However, the results remain uncertain. We carried out a meta-analysis to derive a more comprehensive estimation of the association in Chinese population.MethodsCase-control studies in Chinese and English publications were identified by searching databases of PubMed, EMBASE, Web of Science, CNKI, CBM, Wanfang, VIP and hand searching of relevant journals and the refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 34 publications
6
31
1
1
Order By: Relevance
“…ApoE polymorphisms have been reported to be associated with various diseases, including type II diabetes, coronary artery disease [86,87] , hypertension [15] , Alzheimer's disease [88,89] , and dementia in Parkinson disease [90] . Recently, the associations between ApoE gene polymorphisms and the risk of different subtypes of stroke have been studied extensively [91][92][93] , but the results remain inconclusive, particularly in different ethnic groups and geographical locations.…”
Section: Discussionmentioning
confidence: 99%
“…ApoE polymorphisms have been reported to be associated with various diseases, including type II diabetes, coronary artery disease [86,87] , hypertension [15] , Alzheimer's disease [88,89] , and dementia in Parkinson disease [90] . Recently, the associations between ApoE gene polymorphisms and the risk of different subtypes of stroke have been studied extensively [91][92][93] , but the results remain inconclusive, particularly in different ethnic groups and geographical locations.…”
Section: Discussionmentioning
confidence: 99%
“…It was proven that high plasma concentration of LDL-C increases the risk for cardiovascular disease and HDL-C was beneficial for cardiovascular systems and kidney function and by extracting tissue cholesterol [33,34]. Another study suggested that ε4 increased the level of LDL-C and reduced the level of high density lipoprotein (HDL) in the high-fat intake population [35]. Consistent with our study, Dekroon et al [36] also reported that through altering the components progression of metabolic syndrome, ε4 allele may exert a high risk on cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…(Patients with genotypes ε2/3 and ε2/2 were included in ε2 carriers. Similarly, patients with genotypes ε4/3 and ε4/4 were included in ε4 carriers) [16]. The distribution of genotypes was examined by χ 2 -test to test if it fulfilled the HWE criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Although several recent meta-analyses explored the genetic risk of APOE polymorphisms in CAD [14][15][16], our analysis was the first comprehensive assessment in PCAD. Merging the data of all eligible publications revealed that subjects with the ε4 allele conferred 62% more predisposition to PCAD, while ε4 carriers had 65% higher risk for PCAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation